Enhanced antitumour effect for hepatocellular carcinoma in the advanced stage using a cyclodextrin-sorafenib-chaperoned inclusion complex. (11th September 2019) - Phan, Chiuyen; Zheng, Ziyang; Wang, Jianwei; Wang, Qiwen; Hu, Xiurong; Tang, Guping; Bai, Hongzhen
Abstract : We have proposed and classified the HCC tumor of HCC tumor-bearing BALB/c nude mice to four stages. Cyclodextrin-sorafenib-chaperoned inclusion complexes were prepared and applied to treat advanced HCC tumor-bearing mice. Abstract : Hepatocellular carcinoma (HCC) is a hypervascular tumour characterized by tumour-driven neovascularization. The degrees of blood oxygen saturation (DBOS), microvessel density (MVD) and tumour size (TS) are indicators in identifying the development stage of HCC. Herein, we proposed an HCC staging model using HepG2 tumour-bearing mice based on DBOS, MVD and TS. According to the patterns of these three criteria, HCC was classified into four stages: early, intermediate, advanced and end stages. The advanced stage was characterized by MVD of 50–90 (number per mm 2 ), DBOS of 12–16% and TS of 250–600 mm 3, which poses a critical challenge in HCC therapy. In order to efficiently control and treat HCC in the advanced stage, we developed a cyclodextrin (CD)-based chaperoned inclusion complex using Sorafenib (Sor), β-CD and γ-CD (SCD) via the co-crystallization method. The structural study manifested that CDs could encapsulate Sor with the hydrophobic cavities at a 1 : 1 stoichiometry ratio. The crystallographic analysis indicated that Sor-β-CD presented a diagonal stacking pattern, while Sor-γ-CD possessed a channel-type structure. The resultant chaperoned inclusion complexes significantly improved the solubility, dissolution rate and drug release of Sor, leading to superior pharmacokinetics, biodistribution and biosafety through oral administration. The antitumour effect was then evaluated on a mouse model with advanced HCC through oral administration and intratumour injection. The treatment involving the oral administration of SCDs showed a promising therapeutic effect on advanced HCC, which efficiently blocked angiogenesis and inhibited tumour progression. For the treatments using intratumour injections, only Sor-γ-CD exhibited a satisfactory anti-tumour effect with reduction in TS, MVD and DBOS. The enhanced therapeutic performance of Sor-γ-CD was attributed to its channel-type structure, which had an impact on the dissociation and release of the drug. Thus, Sor-γ-CD can be used as a potential pro-drug for clinical medicine and basic research to treat HCC.